Effect of dental education on peruvian dental students' oral health-related attitudes and behavior - Sato, Manuel (2013)
This study evaluated the effect of dental education on oral health-related attitudes and behavior of students in a five-year dental program in Peru. A survey using the Hiroshima University-Dental Behavioral Inventory (HU-DBI), which consists of twenty dichotomous responses (agree-disagree) regarding oral health behavior and attitudes, was completed by Year 1 and Year 5 dental students at the Universidad Inca Garcilaso de la Vega in Lima, Peru. A total of 153 Year 1 students and 120 Year 5 students responded to the Spanish version of the HU-DBI questionnaire. The data were analyzed using chi-square tests and logistic regression analyses. Compared to the Year 1 students, the Year 5 dental students were more likely to agree with questions such as “I think I can clean my teeth well without using toothpaste” (OR=0.24, 95% CI: 0.10-0.58); “I have used a dye to see how clean my teeth are” (OR=0.19, 95% CI: 0.10-0.36); and “I have had my dentist tell me that I brush very well” (OR=0.34, 95% CI: 0.17-0.69). Overall, the data showed that the curriculum in this dental school in Peru resulted in more positive oral health-related attitudes and behavior among Year 5 dental students compared to those of Year 1 dental students.